Caregiver Perceptions of Infants' and Toddlers' Development of Food-Related Lexicons. (14th June 2022) - Johnson, Susan; Lawless, Megan; Shapiro, Allison
Abstract: Objectives: Children begin to learn words related to food during the complementary feeding period. Their food lexicons and schemas serve as a foundation for building food-related cognitions which, in turn, underpin the development of eating behaviors. We assessed caregiver perceptions regarding young children's food-related receptive and expressive language. Methods: Caregivers, recruited via Qualtrics, reported their perceptions regarding whether their child understood (receptive language) and could say (expressive language) food words (FW; n = 57; e.g., apple) and non-food words related to eating (NFW; n = 73; e.g., cup). Summary scores were derived for receptive and expressive FW and NFW. Mean scores were compared across child age categories (infants 4-< 12 mo, younger toddlers 12-< 18 mo, and older toddlers 18–24 mo) via ANOVA and Scheffe's Test for posthoc group comparisons. General linear models, tested the associations between caregiver sociodemographic factors (age, education, and household income) and receptive and expressive FW and NFW, independent of child age. Results: Caregivers (n = 344; 70.3% female; M ± SD age 31.5 ± 6.3 y), identified as White (73%) and had attended some college (74%). Infants understood significantly fewer FW and NFW compared to younger toddlers (mean difference [95% CL] 12.9 [5.6, 20.2] and 11.1 [4.3, 18.054]; P < 0.05, respectively) and older toddlers (P < 0.05; 19.2 [11.8, 26.6] and 18.5 [11.5, 25.5]; P < 0.05, respectively). Infants and younger toddlers were perceived to speak significantly fewer FW and NFW than older toddlers (mean difference [95% CL]; infants 9.4 [4.4, 14.5] and 14.9 [8.8, 21.0]; young toddlers 6.6 [1.1, 12.2] and 12.3 [5.6, 18.9]). Independent of child age, caregivers reporting the highest household income (>100, 000) perceived children to speak more FW (p = 0.04) and NFW (p = 0.02) than children from households with the lowest reported income (< 26, 000). No other sociodemographic factors were significantly associated with caregiver perceptions of FW understood or spoken. Conclusions: As expected but not previously reported, children's food-related lexical networks increase with age. Household income may exert an influence on children's understanding and use of food words through more complex home environments and greater exposure to a variety of foods. Funding Sources: No funding was received for this work.